2000
DOI: 10.1046/j.1365-2362.2000.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization and characterization of antigen‐presenting dendritic cells in the gastric mucosa of murine and human autoimmune gastritis

Abstract: This is the first report on the localization and phenotypes of DCs in the gastric mucosa of autoimmune gastritis. The presence of mature DCs in the gastric mucosa of murine and human autoimmune gastritis, in spite of their absence in the gastric mucosa of normal mice, suggests that mature DCs play a role in the pathogenesis of autoimmune gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…For humans, only one report has described the presence of a DC subpopulation in an H. pyloripositive MALT lymphoma (40). In the present study, there were no DCs in the gastric mucosa of normal mice, as has been suggested by other workers (31), and only a few myeloid and lymphoid DCs were present in the bottom portion of the lamina propria and in the submucosal area of the gastric mucosa of nTx mice that were not infected with H. pylori. The most noteworthy finding in this study was that in contrast to the noninfected nTx mice, a large number of myeloid DCs were diffusely infiltrated throughout the lamina propria in the H. pylori-infected nTx mouse stomachs, although the degree of lymphoid DC infiltration was not changed by H. pylori infection.…”
Section: Vol 71 2003 Dcs In H Pylori-induced Follicular Gastritis supporting
confidence: 85%
“…For humans, only one report has described the presence of a DC subpopulation in an H. pyloripositive MALT lymphoma (40). In the present study, there were no DCs in the gastric mucosa of normal mice, as has been suggested by other workers (31), and only a few myeloid and lymphoid DCs were present in the bottom portion of the lamina propria and in the submucosal area of the gastric mucosa of nTx mice that were not infected with H. pylori. The most noteworthy finding in this study was that in contrast to the noninfected nTx mice, a large number of myeloid DCs were diffusely infiltrated throughout the lamina propria in the H. pylori-infected nTx mouse stomachs, although the degree of lymphoid DC infiltration was not changed by H. pylori infection.…”
Section: Vol 71 2003 Dcs In H Pylori-induced Follicular Gastritis supporting
confidence: 85%
“…Time course studies in PC-GMCSF transgenic mice indicate that macrophages and dendritic cells precede the influx of CD4 T cells and B cells, supporting the critical role of antigen-presenting cells in the early phase of the autoimmune response (47). A role for dendritic cells has recently been implicated in human autoimmune gastritis (49).…”
Section: Environmentalmentioning
confidence: 85%
“…CCL19 and CCL21 are expressed in the T-cell zone of secondary lymphoid organs, where they exert potential chemotactic action for mature DCs through the interaction with CCR7, promoting immune and inflammatory processes [16, 17,24]. In fact, DCs with the mature phenotype have been identified in gastric mucosa in humans and mice with autoimmune gastritis [25], suggesting that they might contribute to gastric inflammation. A recent in vitro study has shown that DCs express CCR7 and migrate in response to CCL19 after exposure to H. pylori [24].…”
Section: Discussionmentioning
confidence: 99%